2020
DOI: 10.31618/2658-7556-2020-19
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Multi-Element Coatings Before and After Exposure to Laser Radiation

Abstract: It is shown in this work that the effect of laser action on nanostructured coatings can be quite diverse. In this case, the decisive role is played by the initial structure of the coating, which sets the mechanism and direction of its transformation under external, including laser, influences. It is shown that for a CrMnSiCuFeAlTi coating in an argon atmosphere, the friction coefficient after laser treatment decreases, while the microhardness increases. We associate the first effect with a decrease in the roug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…However, later it was shown that simple structures do not always arise, but also Laves phases and several other phases are formed [4][5][6][7][8][9]. This is especially evident in equiatomic structures obtained by mechanical alloying and magnetron sputtering of targets [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…However, later it was shown that simple structures do not always arise, but also Laves phases and several other phases are formed [4][5][6][7][8][9]. This is especially evident in equiatomic structures obtained by mechanical alloying and magnetron sputtering of targets [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Один из перспективных способов упрочнения алюминия и алюминиевых сплавов -это легирование поверхностного слоя другими металлами (Ni, Fe, Co, Cr и др.) и неметаллами (B, Si) с помощью импульсного лазерного воздействия [8][9][10]. Обычно легирующие компоненты представляют из себя порошок, из которого добавлением связующего делают обмазку, наносимую на поверхность изделия и впоследствии обрабатываемую лазером [11].…”
Section: Introductionunclassified